2022
DOI: 10.1186/s12910-022-00758-z
|View full text |Cite
|
Sign up to set email alerts
|

Trust and digital privacy in healthcare: a cross-sectional descriptive study of trust and attitudes towards uses of electronic health data among the general public in Sweden

Abstract: Background The ability of healthcare to protect sensitive personal data in medical records and registers might influence public trust, which in turn might influence willingness to allow healthcare to use such data. The aim of this study was to examine how the general public’s trust relates to their attitudes towards uses of health data. Methods A stratified sample from the general Swedish population received a questionnaire about their willingness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Participants’ willingness to share their PHI depended not only on whom they were sharing it with but also on how their PHI was to be used and for what purpose. Belfrage et al [ 109 ] found that most survey participants would not allow their EHR data to be used for quality assurance, research, or clinical education. In contrast, those who were more trusting of the health care system were more willing to permit these uses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants’ willingness to share their PHI depended not only on whom they were sharing it with but also on how their PHI was to be used and for what purpose. Belfrage et al [ 109 ] found that most survey participants would not allow their EHR data to be used for quality assurance, research, or clinical education. In contrast, those who were more trusting of the health care system were more willing to permit these uses.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, participants with high levels of distrust in the health care system and those without a usual source of care were less supportive of secondary uses of their electronic PHI [ 110 ]. A Swedish health system user survey also found that participants with a self-reported health status of “good or very good” had higher trust in the health care system than those with a “bad or very bad” self-reported health status [ 109 ]. A focus group study by Murphy et al [ 111 ] found that, after headlines about the Cambridge Analytica scandal emerged, participants acknowledged a greater responsibility toward protecting their PHI; however, many participants did not act to safeguard their PHI further.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the acceptance of new technologies lies in cultural aspects (e.g., perceived ease of use, perceived usefulness, trust in personal data management, and others). The above raises an important aspect of sensitizing telemedicine professionals and their users to cultural issues where the adoption of standard definitions and protocols could help overcome these issues [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Notwithstanding that in 2002, Loane raised concerns regarding the scarcity of guidelines and standards in telemedicine, the selected studies did not assess the issue [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its importance has been further highlighted in the response to the COVID-19 pandemic. [13][14][15] Public trust is particularly important for the success of a range of data-driven health system activities such as public uptake of contact tracing apps during the COVID-19 pandemic, [16][17][18][19] public and professional acceptance of artificial intelligence applications in health care, [20][21][22] the establishment of integrated electronic health data records and personal data sharing, [23][24][25][26][27] donation of bio samples and personal data for research purposes [28][29][30] and the public acceptance of digital health provision more broadly. 31 Research in this area shows that public trust is a complex phenomenon that is not easy to maintain and build.…”
Section: Introductionmentioning
confidence: 99%